Urgent Work: Developing a Gender- Responsive Approach for Girls in the Juvenile Justice System (2012)
This paper reviews the prevalence of girls in the U.S. juvenile justice system, compares national and international incarceration rates, and reviews the profile needs of justice-involved girls. The authors offer their Model as an example of how to develop a gender-responsive approach to girls in the justice system, including a description of how the model was operationalized in a community in the United States. Critical developments and emerging opportunities for each of the Model’s components: advocacy, model programming, public education, training and technical assistance, gender responsive tools, systems accountability, and evaluation are highlighted. Lessons learned are offered as a springboard for conversations about how the international community can individually assess their needs and resources and work together to improve the response to girls. The paper concludes with recommendations for choosing, evaluating, and implementing bestpractice approaches for meaningful reform.